2013
DOI: 10.1007/s10461-013-0588-8
|View full text |Cite
|
Sign up to set email alerts
|

Incentivizing HIV/STI Testing: A Systematic Review of the Literature

Abstract: Suboptimal HIV/STI testing uptake has a profound impact on morbidity and mortality. Incentives have been effective in other areas of medicine and may improve HIV/STI testing uptake rates. This study reviewed the effects of incentives on HIV/STI testing uptake. A systematic search of seven databases was undertaken. Testing uptake was defined as test implementation and/or test result retrieval. Incentives were defined as monetary or non-monetary rewards or free-of-charge testing vouchers. Seven studies were incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 85 publications
(78 citation statements)
references
References 42 publications
(100 reference statements)
3
71
0
1
Order By: Relevance
“…21 However, despite growing interest in using incentives to promote HIV-related behaviors such as HIV testing uptake, linkage to HIV care, and retention in care, evidence from randomized trials has been limited. 2226 This study illustrates the strengths and limitations of using incentives as a strategy for modifying such behaviors and preventing new HIV infections.…”
Section: Discussionmentioning
confidence: 91%
“…21 However, despite growing interest in using incentives to promote HIV-related behaviors such as HIV testing uptake, linkage to HIV care, and retention in care, evidence from randomized trials has been limited. 2226 This study illustrates the strengths and limitations of using incentives as a strategy for modifying such behaviors and preventing new HIV infections.…”
Section: Discussionmentioning
confidence: 91%
“…The starting point for all interventions must still be HIV counseling and testing. Innovative ways to promote testing have shown promise including incentivization, self-testing, and mobile health 29,30 but more evaluation to show effectiveness in this age group is required. Comparison of those who tested and those who did not test demonstrated that a higher proportion of those who did not test 36% had less than senior secondary school education compared to 12% for those who tested, suggesting the importance of education on HIV testing.…”
Section: Discussionmentioning
confidence: 99%
“…Among youth aged 12–15 years, 12.7% more individuals tested at the youth centre compared to the clinic [22]. A recent systematic review evaluating the effects of incentives on HIV and sexually transmitted infection testing uptake (7 studies of monetary or non-monetary rewards, including 3 studies described above [1921]) all demonstrated higher uptake in the incentivized groups; the greatest effect was at non clinic-based testing sites [23]. …”
Section: Hiv Testingmentioning
confidence: 99%